Effects of camellia oil on the properties and molecular forces of myofibrillar protein gel induced by microwave heating. (17th May 2021) - Han, Keying; Feng, Xiao; Yang, Yuling; Wei, Sumeng; Tang, Xiaozhi; Li, Shanshan; Chen, Yumin
Abstract: The effects of camellia oil (CO) addition (0–50 mg·mL −1 ) on the properties, structures and molecular forces of chicken myofibrillar protein (MP) gel induced by microwave heating were studied. Results indicated that the hardness, gumminess, chewiness and water holding capacity of the gel (50 mg·mL −1 MP) were the highest after 40 mg·mL −1 CO addition. For 40 mg·mL −1 CO addition, the gel network was more homogeneous, and the hydrophobic interaction of MP reached the maximum according to the S0 ‐ANS values, while electrostatic repulsion was the minimum according to the zeta potential. The α‐helix content decreased and the β‐sheet content increased as CO concentration increased from 0 to 40 mg·mL −1 . Increased CO induced the unfolding of MP molecules and exposure of internal hydrophobic groups, which affected the hydrophobic interaction and the gel properties. To conclude, 40 mg·mL −1 of CO was the optimal amount to prepare composite gel when MP was 50 mg·mL −1 . Abstract : Camellia oil (CO) addition significantly increased the WHC and whiteness of myofibrillar protein (MP) gel. For 40 mg·mL −1 CO addition, the gel network was more homogeneous, the hydrophobic interaction of MP reached the maximum. The α‐helix content decreased and the β‐sheet content increased as CO concentration increased from 0 to 40 mg·mL −1 .